The effectivity of cavity cleanser chlorhexidinegluconate 2% and saponin 0.78% of mangoosteen peel - Maretha Siwinata; Nanik Zubaidah; Adioro Soetojo (Universitas Airlangga, 2020)
Background. Use of cavity cleanser is important before restoration the teeth to clean debris, residue of prepared dentine, blood, bacteria, collagen denaturized by teeth preparation. Nowadays, the cavity cleanser that people used still having shortcoming, one of which is the lack of ability to clean the root canal of the smear layer. Purpose. The purpose of this study examines the difference of cavity cleaner between saponin of mangoosteen peel (GarciniaMangostana L.) and chlorhexidinegluconate 2%. Method. Eighteen upper first premolar divided into 3 groups, each of them consist three tooth. Forming the preparation tooth cavity then group 1 using aquadest for control group, group 2 using chlorhexidinegluconate 2%, and group 3 using saponin of mangoosteen peel (GarciniaMangostana L.). For rating cleanliness of the tooth cavity using a scale of cleanliness conducted under Scanning Electron Microscope. Result. There was a significant difference (p < 0.05) in One-Way ANOVA parametric test andpos hoc test between chlorhexidinegluconate 2 % and saponin of mangoosteen peel to the cleanliness of the tooth cavity. Conclusion.According to the result of the study, it can be concluded that saponin of mangoosteen peel (GarciniaMangostana L.) less effective for cleaning the tooth cavity than chlorhexidinegluconate 2%.